Educator Strategies for Addressing Individual Differences in the Learning Process - Raranta, Joice Ester; Tando, Djanne (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
When it comes to the learning process, it is not enough for the instructor to just transfer the material, or what is more frequently referred to as the transfer of knowledge. Because there are various components of learning that need to be assessed by teachers on their pupils, including cognitive aspects, emotional aspects, and psychomotor aspects. This is because learning encompasses all of these characteristics. Therefore, in order to realize learning goals with the best possible results, it is necessary for teachers to have an understanding of the peculiarities of each student. We are going to discover that individual variation is typically the result of the simultaneous interplay between hereditary factors and environmental impacts, which finally results in the production of a one-of-a-kind human person. Therefore, in order to be an effective educator, one must have the ability to comprehend the qualities and features of each unique pupil. In a certain manner or approach, and then directly implement it in the learning process, so that they are aware of the differences between their pupils and how to overcome them in ways that are simple for students to grasp or understand.